sole4 - ANALYSIS EXERCISE 4SOLUTIONS 1. (a) Let x1 , x2 X...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
ANALYSIS EXERCISE 4–SOLUTIONS 1. (a) Let x 1 ,x 2 X be arbitrary. Suppose that g ( f ( x 1 )) = g ( f ( x 2 )). Then f ( x 1 ) = f ( x 2 ) since g is injective. Therefore x 1 = x 2 since f is injective. This proves that g f is injective. (b) Let z Z be arbitrary. Then y Y such that g ( y ) = z since g is surjective. Also x X such that f ( x ) = y since f is surjective. Therefore we have proved ( z Z )( x X )[ g ( f ( x )) = z ] . So g f is surjective. 2. (a) Let z Z . Then ( x X )[( g f )( x ) = z ] as g f is surjective. So g ( y ) = z where Y 3 y = f ( x ), thus g : Y Z is surjective. (a) Let y Y . Put z := g ( y ) Z . As g f is surjective, ( x X )[( g f )( x ) = z ]. But then z = g ( y ) = ( g f )( x ) = g ( f ( x )) . As g : Y Z is injective, it follows that y = f ( x ). In other words, ( x X )[ f ( x ) = y ] and hence f is surjective. 3. The composition g f : R - {- 1 , 1 } → R is defined by ( g f )( x ) = 1 f ( x ) = x - 1 x + 1 . 4. (a)
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Image of page 2
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 02/25/2010 for the course MATHEMATIC 11007 taught by Professor Spyros during the Winter '10 term at Bristol Community College.

Page1 / 3

sole4 - ANALYSIS EXERCISE 4SOLUTIONS 1. (a) Let x1 , x2 X...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online